Jubran Khalil Jubran’s wisdoms (quotes) and their symmetries in Wisam Al Haddad's ceramics - Weam Qais Younis, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research addressesJubran Khalil’s wisdoms (quotes) and their symmetry in the ceramics of Wisam Al Haddad. The research is composed of four chapters;the first chapteraddresses the methodological framework for the research represented by the research problem and its importance, which ends with the following question: - Are there symmetries of Gibran Khalil Gibran’s wisdoms in the ceramics of Wisam Haddad? The significance of research:Highlighting aremarkable figure in the history of Arabic poetry, namely, Gibran Khalil Gibran.Enriching art libraries with a study of one of the cognitive concepts regarding quotes and their inspiration in ceramics . Finally, presenting to all humanity a tremendous heritage that is still a focus of attention of researchers and artists in this field.